2016
DOI: 10.1002/hec.3323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physician-directed Pharmaceutical Promotion on Prescription Behaviors: Longitudinal Evidence

Abstract: Spending on prescription drugs (Rx) represents one of the fastest growing components of U.S. healthcare spending, and has coincided with an expansion of pharmaceutical promotional spending. Most (83%) of Rx promotion is directed at physicians in the form of visits by pharmaceutical representatives (known as detailing) and drug samples provided to physicians' offices. Such promotion has come under increased public scrutiny, with critics contending that physician-directed promotion may play a role in raising hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Yeh et al used a 2011 cross section of Massachusetts physicians to examine transfers and Medicare part D statin prescriptions and found that transfers were positively associated with branded prescriptions. Datta and Dave use a longitudinal monthly dataset on 150 000 physicians spanning 1997‐1999 to examine the effects of industry detailing on prescriptions for the detailed drug and found a positive relationship. Carey et al examined the impact of pharmaceutical transfers on prescribing behavior under Medicare Part D from 2011 to 2013 and found that patients are more likely to be prescribed a drug when their prescriber received a transfer from its company; however, examining efficacy data from clinical trials, they find that those receiving transfers are more likely to prescribed higher quality drugs on average.…”
Section: Existing Literaturementioning
confidence: 99%
“…Yeh et al used a 2011 cross section of Massachusetts physicians to examine transfers and Medicare part D statin prescriptions and found that transfers were positively associated with branded prescriptions. Datta and Dave use a longitudinal monthly dataset on 150 000 physicians spanning 1997‐1999 to examine the effects of industry detailing on prescriptions for the detailed drug and found a positive relationship. Carey et al examined the impact of pharmaceutical transfers on prescribing behavior under Medicare Part D from 2011 to 2013 and found that patients are more likely to be prescribed a drug when their prescriber received a transfer from its company; however, examining efficacy data from clinical trials, they find that those receiving transfers are more likely to prescribed higher quality drugs on average.…”
Section: Existing Literaturementioning
confidence: 99%
“…Drug promotion reduces cost efficiency by, for example, increasing use of expensive drugs instead of cheaper, equally safe and effective alternatives (such as branded instead of generic) 23242526. This creates financial burdens for individuals and opportunity costs to society, and threatens the sustainability of the healthcare system.…”
Section: Why Drug Promotion Is An Urgent Problemmentioning
confidence: 99%
“…This places our study in contrast to Carey et al (2017), Datta and Dave (2016), Mizik and Jacobson (2004), in which the researchers include physician fixed effects to take out persistent unobserved differences across physicians. 32 The average treatment effect of a pharmaceutical firm providing one fewer meal to a physician in the context of a long physician-firm relationship, or of providing the first meal to a physician at the initiation of a physician-firm relationship, may be very different than the average treatment effect of turning an entire relationship on or off.…”
Section: A Note On "Meals" and Cross-sectional Identificationmentioning
confidence: 99%
“…In order to examine the interactions between market power and payments to physicians, we estimate a nested logit model of statin choice, integrating our demand estimation with the machine learning procedures from Belloni et al (2017), similar to Gillen et al (2015). 8 At least two other published studies we are aware of incorporate physician-level fixed effects: Mizik and Jacobson (2004) and Datta and Dave (2016). In a market such as statins, where relationships likely pre-date the beginning of the payment data, a fixed effect intuitively controls for the unobserved relationship.…”
Section: Introductionmentioning
confidence: 99%